299. Prostate cancer dose-fraction sensitivity deduced from radiotherapy outcome of 17949 patients. (December 2018) - Maggio, A.; Tamponi, M.; Gabriele, D.; Conti, M.; Meloni, G.B.; Gabriele, P.; Stasi, M.
Abstract : Purpose: Aim of the work is to model biochemical free survival at five year (5 y BCFS), based on literature clinical outcome data available until now and to evaluate parameters describing dose-fractionation radiosensitivity and repopulation. Methods: Twenty-six data sets published in literature reporting the 5 y BCFS, dose scheduling, androgen deprivation therapy (ADT) and clinical variables, have been considered for a total of 17949 prostate cancer patients treated with external beam radiation therapy (EBRT), with and without ADT with dose per fraction from 1.80 Gy/fr to 7.25 Gy/fr and overall treatment time (OTT) from 1 week to 10 weeks. Fifteen patients groups have been built considering the risk class and the use of ADT. At first, for each group, D50 and g50 parameters were calculated. Then, dprolif, Tprolif and α / β parameters have been evaluated considering three hypothesis: dependence and not on OTT and dependence only on OTTs difference. Results: The median values of D50 and g50 were 57 Gy and 1.7 for low risk patients, 61 Gy and 1.8 for intermediate risk patients and 68 Gy and 1.9 for high risk patients. For intermediate and high risk patients, a reduction of 4 Gy for D50 and 0.5 for g50 for ADT respect to no ADT treated patients was found. Not considering OTT dependence, the median α / β value parameter was in the range 0.8 Gy–2.6 Gy for the groups analysed. Median value of the dprolif was in the range 0.0 Gy/d–0.3 Gy/d while a median value of Tprolif parameter greater than 20 days was obtained. Conclusions: Low α / β values have been confirmed for each risk class and the use of ADT seems to reduce median α / β values for intermediate and high risk patients. α / β values lower than values for late normal tissue morbidity increase and support the interest of hypofractionated radiotherapy schedules for all risk groups.